Composite Structures with Emissive Quantum Dots for Light Enhancement. Issue 4 (6th November 2018) - Smith, Marcus J.; Lin, Chun Hao; Yu, Shengtao; Tsukruk, Vladimir V.
Abstract: Since their inception, quantum dots have proven to be advantageous for light management applications due to their high brightness and well‐controlled absorption, scattering, and emission properties. As quantum dots become commercially available at large scale, the need for robust, stable, and flexible optical components continues to drive the development of robust and flexible quantum dot composite materials. In this review, after a thorough introduction to quantum dots, discussion delves into methods for fabricating quantum dot loaded composite optical elements such as thin films, microfabricated patterns, and microstructures. The importance of surface chemistry and ligand engineering, host matrixes, wet processing, and unique patterning methodologies is presented by considering photostability, aggregation, and phase separation of quantum dots in corresponding composites. With regard to prospective optical applications of quantum dot materials, emphasis is placed on light emitting and guiding composite materials for lasing applications, specifically whispering gallery mode‐based photonic microsystems. These developments will enable novel flexible, portable, and miniaturized optoelectronic devices such as light‐emitting diodes, flexible pixelated displays, solar cells, large‐area microwaveguides, omnidirectional micromirrors, optical metasurfaces, and directional microlasers. Abstract : Herein the state of the art of quantum dot composite materials is described, with particular interest paid to light emitting and guiding technologies. Great attention is paid to micropatterning, focusing on the importance of surface chemistry and ligand engineering, host matrixes, and wet processing to achieve optimal photostability, aggregation, and phase separation of quantum dots in corresponding patterns and resulting devices.